The Role of Microbiota in Neutrophil Regulation and Adaptation in Newborns - Lajqi, Trim; Pöschl, Johannes; Frommhold, David; Hudalla, Hannes (Frontiers in Immunology, 2020)
Newborns are highly susceptible to infections and mainly rely on innate immune functions. Reduced reactivity, delayed activation and subsequent failure to resolve inflammation however makes the neonatal immune system a very volatile line of defense. Perinatal microbiota, nutrition and different extra-uterine factors are critical elements that define long-term outcomes and shape the immune system during the neonatal period. Neutrophils are first responders and represent a vital component of the immune system in newborns. They have long been regarded as merely executive immune cells, however this notion is beginning to shift. Neutrophils are shaped by their surrounding and adaptive elements have been described. The role of “innate immune memory” and the main triangle connection microbiome – neutrophil – adaptation will be discussed in this review.